The platform behind the curtain: Obfuscated brokerage on retail trading platforms - Andreas Gregersen; Jacob Ørmen (Internet Policy Review, 2024)
Retail trading platforms have gained popularity in recent years as brokers for ordinary people to trade speculative assets such as stocks and cryptocurrencies. These platforms earn revenue from their users' risky trading and through derivative products, where the platform benefits as the traders lose. The platforms thus operate with conflicts of interest: what is good for the platform and its users are not necessarily the same. We explore how retail trading platforms navigate these conflicts of interest in a case study of the global and multi-asset broker eToro. Through an analysis of three different types of brokerage - financial, informational, and social - we show how the platform obfuscates its roles and operations to mask underlying conflicts of interest. In the end, we argue that the interweaving of brokerage roles compounds platform power as platforms can exploit their gatekeeping position and information asymmetry to promote their preferred transactions at the expense of users and complementors. The analysis thus contributes both to the specific understanding of retail trading platforms and to the general discussion of conflicts of interest in platform power.
Keywords: 300; Brokerage; Platform power; Retail trading platform; Investment; Conflict ofinterest